The digital signal processor Derby. - Eyre, J. (IEEE spectrum)
Applications that use digital signal processing chips are flourishing, buoyed by increasing performance and falling prices. Concurrently, the market has expanded enormously. Vendors abound. Many newcomers have entered the market, while established companies compete for market share by creating ever more novel, efficient, and higher-performing architectures. The range of digital signal-processing (DSP) architectures available is unprecedented. In addition to expanding competition among DSP processor vendors, a new threat is coming from general-purpose processors with DSP enhancements. So, DSP vendors have begun to adapt their architectures to stave off the outsiders. The author provides a framework for understanding the recent developments in DSP processor architectures, including the increasing interchange of architectural techniques between DSPs and general-purpose processors